Faktor-Faktor Yang Berhubungan Dengan Kejadian Luka Tusuk Jarum Suntik Pada Perawat Di Rumah Sakit Bhayangkara Brimob Tahun 2018 - Indri Meilawati; Yuli Prapancha; Teguh Wiyono (Universitas Respati Indonesia, 2019)
Background:Syringe injuries are the most frequent workplace accidents in hospitals. The data showed that the incidence of needle stick injuries in Nurses at Bhayangkara Brimob Hospital in 2018 contained 11 cases of syringe injuries. The purpose of this study was to determine what factors related to the incidence of syringe injuries to nurses in 2018.Method: This type of quantitative research uses a cross-sectional approach. This study was conducted in May 2018 until July 2018. The study sample used total sampling, with the number of respondents obtained by 53 people. Data collection using a questionnaire. The statistical test used is the regression coefficient test.Result and Discussion: Based on the results of statistical tests showed that age was associated with the incidence of needle stick injuries (t = 0.004), the period of service had no relationship with the incidence of syringe injuries (t = -1.939> -2.013), the use of PPE was not related to the incidence of NSI (t = 0.711 <2.013), the participation of nurses in K3 / PPI RS training is related to the incidence of NSI (t = 2.468> 2.013).Conclusions and Suggestion: Age factor influences the incidence of syringe, working period has no effect on the incidence of syringe injury, tioak APD use factor has an effect on the incidence of syringe injury, the factor of nurses' participation in K3 / PPIRS training affects the incidence of syringe injury in bhayangkara brimob hospital. The advice that can be done is to conduct training and deepening the material for safe injecting practice to all nurses on a regular basis.Keywords: Needle Stick Injurie, Work incident